Direct conversion of furfural to 1,5-pentanediol over a nickel–cobalt oxide–alumina trimetallic catalyst - Kurniawan, Rizky Gilang; Karanwal, Neha; Park, Jaeyong; Verma, Deepak; Kwak, Sang Kyu; Kim, Seok Ki; Kim, Jaehoon (Applied Catalysis B: Environmental, 2023)
The use of a Ni–CoOx–Al2O3 mixed metal–metal oxide catalyst was proposed for the one-pot direct conversion of furfural (FFA) to 1,5-pentanediol (1,5-PDO), which afforded a high yield (47.5%) at 160 °C and at an initial H2 pressure of 3 MPa for 6 h in ethanol. Proximity between the Ni0 and oxygen-vacant CoOx (Ov–CoOx) sites favored the dissociative adsorption of H2 molecules on Ni0 and subsequent hydrogen spillover to Ov–CoOx. The hydrogenation of the C[dbnd]O group of FFA produced furfuryl alcohol, which was then adsorbed on the Coδ+ center of the Ov–CoOx site in a η1–(O)–alcoholic configuration, where subsequent C–O bond cleavage produced 1,5-PDO. Catalytic activity loss through the oxidation of the Ni0 and Ov sites could be mitigated by reactivation under H2. Thus, the developed Ni–CoOx–Al2O3 catalyst has potential for efficient, low-cost, and environmentally friendly 1,5-PDO production from FFA.
Keywords: 5-pentanediol; Direct conversion; Dissociative adsorption; Higher yield; Metal oxides catalysts; Mixed-metals; Nickel cobalt oxides; One pot; Orthogonal space-time block coded systems; Trimetallic catalysts; 1; 5-Pentanediol; Cobalt; Direct conversion; Furfural; Nickel; Oxygen vacancy